Revisiting the choice of teaching methods in mathematical training of a future primary school teacher - N. M. Evtykhova (Вестник Майкопского государственного технологического университета, 2025)
Abstract. The relevance. The problem of choosing teaching methods has always caused many difficulties. Currently, pedagogical science has accumulated a fairly large arsenal of pedagogical techniques and methods, and in recent years, the digital transformation of the entire education system has become relevant. In these conditions, the organization of students' educational activities, the choice of effective teaching methods becomes a rather difficult task for a teacher.The most important component of the education of a modern primary school teacher is his/her subject competence, which includes mathematical competence. Mathematical training of future primary school teachers involves formation of functional mathematical literacy of students and includes a deep knowledge of the theoretical foundations of the basic course of Mathematics, the ability to apply them in practical activities. Despite the existing fairly large number of publications, it is difficult to find studies reflecting a harmonious combination of traditional and digital technologies in the subject (in particular, mathematical) training of future primary school teachers, which allows us to talk about the relevance of this topic.The problem of the research is to identify the most effective pedagogical methods and technologies and digitalization of the educational process in the context of blended learning of Mathematics for future primary school teachers. The fundamental task is to study the educational process of primary general education in the context of digitalization, both of the entire life of society and of education, to describe possible models of organizing the educational process and correcting the content of education, taking into account the requirements put forward by digitalization.The goal of the research is to show the need for a competent combination of traditional and innovative technologies and methods of teaching Mathematics to future primary school teachers in the new conditions of digital transformation of education.The research methods used are analysis of literature on the topic of the research, observation, generalization of the experience of applying various pedagogical technologies and methods in the educational activities of students – future primary school teachers. General logical methods of scientific research have been used.The research results and conclusions: regulatory documents have been analyzed and summarized, application of modern technologies, including digitalization of educational activities have been studied, and a model of the process of teaching mathematics to future primary school teachers has been presented. The research has revealed the need to develop teaching aids in traditional and digital form for the implementation of this model in the educational process.